3D Simulations of the Early Martian Hydrological Cycle Mediated by a H2‐CO2 Greenhouse. Issue 7 (14th July 2021) - Guzewich, Scott D.; Way, Michael J.; Aleinov, Igor; Wolf, Eric T.; Del Genio, Anthony; Wordsworth, Robin; Tsigaridis, Kostas
Abstract: For decades, the scientific community has been trying to reconcile abundant evidence for fluvial activity on Noachian and early Hesperian Mars with the faint young Sun and reasonable constraints on ancient atmospheric pressure and composition. Recently, the investigation of H2 ‐CO2 collision‐induced absorption has opened up a new avenue to warm Noachian Mars. We use the ROCKE‐3D global climate model to simulate plausible states of the ancient Martian climate with this absorptive warming and reasonable constraints on surface paleopressure. We find that 1.5–2 bar CO2 ‐dominated atmospheres with ≥3% H2 can produce global mean surface temperatures above freezing, while also providing sufficient warming to avoid surface atmospheric CO2 condensation at 0°–45° obliquity. Simulations conducted with both modern topography and a paleotopography, before Tharsis formed, highlight the importance of Tharsis as a cold trap for water on the planet. Additionally, we find that low obliquity (modern and 0°) is more conducive to rainfall over valley network locations than high (45°) obliquity. Plain Language Summary: Much evidence tells us that ancient Mars had liquid water on its surface. But reconciling that with the fainter young Sun and reasonable constraints on Mars' early atmosphere is challenging. We use a 3D global climate model with an atmosphere containing some amount of hydrogen (a possible greenhouse gas) to study Mars' early hydrological cycle and compare it to the geological evidence of surface liquid water billions of years ago. We find that hydrogen and carbon dioxide together in an atmosphere twice as thick as modern Earth can warm early Mars above the freezing point of water and that a low axial tilt produces rainfall patterns that best match the geologic evidence. Key Points: A H2 ‐CO2 Greenhouse can warm early Mars above the freezing point of water Low obliquity is more conducive to rainfall over locations with valley network formations Fully coupled dynamic oceans in the northern hemisphere or Hellas basin do not significantly alter the ancient climate